Endoscopic management of anastomotic leakage after colorectal cancer surgery in a Moroccan center: A case series and literature review - Benayad Aourarh; Amine Souadka; Mohamed Anass Majbar; Amine Benkabbou; Amal Chakkor; Meriem Bakkar; Raouf Mohsine; Laila Amrani (SAGE Open Medical Case Reports, 2023)
Endoscopic management has become an alternate treatment to a revision surgery for colorectal fistulas. Eight patients who were treated by endoscopy for postoperative anastomotic leakage to colorectal cancer were included. A univariate analysis was carried out to determine the predictive factors of success. All our patients were treated using metallic clips. The primary efficiency of this technique was 50%. In a univariate analysis, the size of the fistula and its distance from the anal margin had an influence on the efficiency of the endoscopic treatment, which was not the case for either the surgical technique or the use of neoadjuvant radiotherapy. This endoscopic treatment is effective and represents a more secure alternative than revision surgery. In our study, the use of metallic clips showed a 50% success rate, going up to 100% for the group of patients with a fistula ostium of a size ⩽1 cm, proving the necessity of using this technique.